PENERAPAN METODE MASSAGE ENDORPHIN DAN OKSITOSIN TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU MENYUSUI BAYI 0-6 BULAN DI DESA GADING KABUPATEN PROBOLINGGO - hidayati, tutik; hanifah, iis (Jurnal Ilmiah Kesehatan, 2019)
Milk is produced by releasing the hormone oxytocin through the ducts in the breast. The growth and development of a baby's brain nerve requires high-value nutrients by giving the mother's milk to the baby. One of the obstacles in giving ASI early is the production of less milk in the first days. The length of time spent breastfeeding is influenced by the hormone oxytocin and the hormone prolactin which can be released by means of endorphin and oxytocin masage is done by gentle caress first and then massage on the back. endorphin and oxytocin masage is an intervention that is expected to help post partum mothers facilitate breast milk production. Rusdiati's 2013 results show that there is an effect of oxytocin massage on breastfeeding in postpartum mothers. The results were obtained after oxytocin massage ASI out faster than not done oxytocin massage. This study used a pre-experimental design with one group pre test post test design method. The population is all mothers who breastfeed babies aged 0-6 months. The sampling technique used is total samling. Data analysis using Wilcoxon obtained the results of ? = 0,000, so that ? <? = 0.05, then there is the influence of the Application of Masage Endorphin and Oxytocin Method to Increased Breast Milk Production in Breastfeeding Mothers of Babies 0-6 Months in Gading Village. Health workers, especially midwives, are expected to provide health education and training on endorphin and oxytocin massage in nursing mothers.